Student Entrepreneur: Antecedents and Consequences of Intrinsic Motivation - Ellyana Amran; Hermanto Yaputra (Indonesia Marketing Association (IMA), 2023)
Entrepreneurship is an important economic driver by fostering an entrepreneurial spirit, which can be trusted as a solution to limited employment opportunities and poverty alleviation. Intrinsic Motivation is the key to the success of student in entrepreneurship. This study aims to explain the effect of entrepreneurship education and social norms on entrepreneurial intention which is mediated by the intrinsic motivation of student. Sampling using purposive sampling technique, a total of 108, with quantitative approach, data were collected using Structural Equation Model. The research findings are that there is no influence of entrepreneurship education on entrepreneurial intention; there is a positive influence of social norms on entrepreneurial intention; Intrinsic motivation can moderate the relationship between entrepreneurship education and entrepreneurial intentions; Intrinsic motivation can moderate the relationship between social norms and entrepreneurial intentions.